Evaluation of acute toxicity and effect of picositol in letrozole induced polycystic ovarian syndrome in animal models - Tung, Tran Thanh; Hien, Dang Thi Thu (Tạp chí Nghiên cứu Y học, 2026)
This study aims to investigate the acute toxicity and the therapeutic potential of Picositol in a letrozole-induced PCOS model in Wistar rats. An acute toxicity study of Picositol by administering a single dose (5000 mg/kg) was done in rats following OECD guideline 423. For the PCOS-induced experiment, after induction of PCOS by orally administered letrozole (1 mg/kg) for 21 days, female rats were divided into six groups for treatment up to 15 consecutive days. Blood samples were withdrawn at the end of the study for the determination of sex hormone levels, malondialdehyde (MDA), glutathione (GSH), and the relative weight of fat, uterus, and ovaries was separated. The results demonstrated that treatment with Picositol at both doses significantly reduced oxidative stress markers and increased GSH. In addition, the formulation improved endocrine disturbances by lowering testosterone and showing a tendency to increase progesterone, while no improvement in estradiol was observed. Picositol also decreased fat mass and ovarian weight and tended to increase uterine weight relative to the model group. Collectively, these findings indicate that Picositol exhibited no detectable acute toxicity and provided supportive therapeutic effects on experimental polycystic ovary syndrome in Wistar rats.